Quinine pharmacokinetics and toxicity in pregnant and lactating women with falciparum malaria. - Phillips, R; Looareesuwan, S; White, N; Silamut, K; Kietinun, S; Warrell, D (1986)
Quinine dihydrochloride (10 mg or, in two patients, a loading dose of 20 mg kg-1) was infused intravenously over 4 h in ten severely ill but conscious women with falciparum malaria complicating the third trimester of pregnancy. Plasma quinine concentrations, measured spectrophotofluorimetrically after benzene extraction, fitted closely a single exponential decline after the intravenous infusion. These data were therefore fitted to a one compartment model: total apparent volume of distribution, V, 0.96 +/- 0.27 l kg-1 (+/- s.d.), elimination half-time (t1/2,z), 11.3 +/- 4.3 h, total clearance, 1.22 +/- 0.77 ml min-1 kg-1. There was no relationship between arterial blood pressure and plasma quinine concentrations. Eight women delivered of live infants while taking quinine, had placental cord plasma quinine concentrations from 1.0 to 4.6 mg l-1 (mean 2.4) which correlated significantly with maternal plasma quinine concentrations (r = 0.78, t = 3.06, P less than 0.05). The mean (+/- s.d.) ratio of cord plasma to maternal plasma quinine concentration was 0.32 +/- 0.14. Heart blood from a foetus aborted at term had a plasma quinine concentration of 2.8 mg l-1; simultaneous maternal plasma quinine was 7.1 mg l-1 (ratio 0.39). Breast milk quinine concentrations and milk to plasma ratios were 0.5-3.6 mg l-1 (mean 2.6) and 0.11-0.53 (mean 0.31) in twenty-five women who were breast-feeding and had taken oral quinine sulphate for 1-10 days (mean 4.0). Five women with more serious infections received intravenous quinine; breast milk quinine concentrations ranged between 0.5 and 8.0 mg l-1 (mean 3.4).(ABSTRACT TRUNCATED AT 250 WORDS)